MANAJEMEN KEPALA SEKOLAH DALAM MEMBINA DISIPLIN GURU - Muhammad Zaenudin (Manajer Pendididikan, 2016)
The purpose of this research is to describe the principal’s management in developing the discipline of teachers in Public Vocational High School 1 in of Ketahun. The subyect of thisresearch was the principal in Public Vocational High School. The method was designed as descripte qualitative method.The data collecting technique were interview, observation, anddocumentation. The resuls of this research showed that the schools principal’s management on the teachers’ dicipline has been done well and systematic.Keywords: management, principal, discipline, teacher